Eutrophication strengthens the response of zooplankton to temperature changes in a high‐altitude lake. Issue 18 (30th August 2016) - Li, Yun; Xie, Ping; Zhao, Dandan; Zhu, Tianshun; Guo, Longgen; Zhang, Jing
Abstract: To assess whether and how zooplankton communities respond to variations in temperature and how these assemblages change with eutrophication, we performed a large‐scale, monthly survey from August 2011 to July 2012 to determine the seasonal and spatial variations in these communities in a high‐altitude lake. A detrended correspondence analysis and a path analysis demonstrated that temperature and chlorophyll a were important factors influencing zooplankton. The path diagram showed that Daphnia was negatively affected directly by chlorophyll a and indirectly by temperature, whereas Bosmina was directly and positively affected by temperature. Daphnia spp. decreased in both absolute and relative biomass during warm seasons, whereas Bosmina spp. showed the opposite trend. Moreover, the lowest Daphnia spp. biomass was observed in the southern region, which was the most eutrophic. Our results indicate that increasing temperatures will continue to shift the dominant genus from Daphnia to Bosmina, and this change will be exacerbated by eutrophication. In addition, the zooplankton of Lake Erhai have shifted to smaller species over time as temperature and eutrophication have increased, which implies that zooplankton succession to small cladocerans may be markedly accelerated under further climate change and the increased eutrophication that has been observed in recent decades. Abstract : We performed a large‐scale, monthly survey from August 2011 to July 2012 to determine the seasonal and spatial variations in zooplankton communities in a high‐altitude lake. A detrended correspondence analysis and a path analysis demonstrated that temperature and chlorophyll a were important factors influencing zooplankton. Our results indicate that increasing temperatures will continue to shift the dominant genus from Daphnia to Bosmina, and this change will be exacerbated by eutrophication.